Предмет: Алгебра, автор: bondar4yk2008

помогите пожалуста срочно нужно!

Приложения:

Ответы

Автор ответа: sergeevaolga5
1

-6x^{-7}y^5*(-1\frac{1}{6}x^{-2}y^{-2})=-6*(-\frac{7}{6})*x^{-7-2}y^{5-2}=7x^{-9}y^3\\\\(-\frac{2}{5}a^5b)*\frac{15}{16}a^{-7}b^{-1}=-\frac{2}{5}*\frac{15}{16}a^{5-7}b^{1-1}=-\frac{3}{8}a^{-2}b^0=-\frac{3}{8}a^{-2}*1=-\frac{3}{8}a^{-2}\\\\\\\\41000=4,1*10^4\\\\0,04=4*10^{-2}\\\\317,8=3,178*10^2\\\\0,408=4,08*10^{-1}

Похожие вопросы
Предмет: Английский язык, автор: 3216kiska